Modelos y organización de una unidad de consejo genético - Pérez Segura, Pedro (Psicooncología, 2005)
Hereditary cancer affects 5-10% of the oncologic patients that we see ordinary in a medical oncology department. However, the great majority of the oncologist have a little knowledgement about this issue. The molecular and clinical advances in this field has provided us to detect high risk people to suffer some types of cancer, because they are germline mutation carriers in any susceptibility genes (genetic tests) and, also, the possibility of reduce the risk of suffering this disease almost in 100% of the cases (prophylactic surgery).In this paper we analyze the state-of-the-art in some aspects of hereditary cancer and its clinical management, also a little review about the psycological situations in this type of clinical counselling.